A new approach to parameter extraction of a photovoltaic panel: a comparison study - Mesbahi, Oumaima (2020)
The long outside exposure of the photovoltaic panels makes them susceptible to thermal and mechanical shocks, this causes their degradation which can be manifested under many forms like corrosion, discoloration, cracks and shocks. The effect of degradation of photovoltaic modules and their subsequent loss of performance has a serious impact on the total energy generation potential, without neglecting the lack of information of the output power in terms of real time.